2018
DOI: 10.1021/acsomega.7b01689
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of a Novel Thiazoline Core as a Potent Peroxisome Proliferator-Activated Receptor δ Agonist

Abstract: The convergent and enantioselective synthesis of a highly potent human peroxisome proliferator-activated receptor delta agonist is presented. More specifically, the thiazoline structure, which constitutes the biosynthetically distinctive core structure of pulicatin (a secondary metabolite of symbiotic bacteria), was synthesized from a commercially available and inexpensive chiral pool of l-threonine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…From the results of molecular docking studies, in vitro ADME/Tox, and in vivo pharmacokinetic studies, compound 38 demonstrated itself as a promising candidate for the treatment of PPARδ-related diseases. In another study, we reported an enantioselective synthesis of a natural product, pulicatin-inspired, unique methyl-thiazoline-core containing novel compound 39 as a highly potent PPARδ agonist (EC 50 = 6.2 nM) . Furthermore, we recently reported a simple and efficient synthetic route of a dimethyl-thiazoline-core containing compound 40 as a new scaffold for PPARδ agonist …”
Section: Medicinal Chemistry Of Synthetic Pparδ Agonistsmentioning
confidence: 99%
“…From the results of molecular docking studies, in vitro ADME/Tox, and in vivo pharmacokinetic studies, compound 38 demonstrated itself as a promising candidate for the treatment of PPARδ-related diseases. In another study, we reported an enantioselective synthesis of a natural product, pulicatin-inspired, unique methyl-thiazoline-core containing novel compound 39 as a highly potent PPARδ agonist (EC 50 = 6.2 nM) . Furthermore, we recently reported a simple and efficient synthetic route of a dimethyl-thiazoline-core containing compound 40 as a new scaffold for PPARδ agonist …”
Section: Medicinal Chemistry Of Synthetic Pparδ Agonistsmentioning
confidence: 99%
“…Thiazoline scaffolds with an aromatic ring at the C-2 position are common in various biologically active compounds, including natural products such as pulicatins 21 and the highly potent human peroxisome proliferator-activated receptor-δ agonist. 22 The decarboxylative thioacylation between 45 and threonine derivative 46 furnished thioamide 47 in 71% yield, which was directly converted into thiazoline 49 after treatment with N,N-diethylaminosulfur trifluoride (DAST), followed by reduction with DIBAL-H (Scheme 2A). Furthermore, the synthesis of thioacylated lysine compounds, which exhibit anticancer properties, was also accomplished using this thioacylation (Scheme 2B).…”
Section: Scheme 2 Synthetic Applications Of the Decarboxylative Thioacylation Of Amines Amentioning
confidence: 99%
“…To demonstrate its synthetic utility, we applied this chemoselective thioacylation reaction to the synthesis of several biologically active compounds (Scheme A,B). Thiazoline scaffolds with an aromatic ring at C-2 are common in various biologically active compounds, including natural products such as pulicatins and the highly potent human peroxisome proliferator-activated receptor-δ agonist . The decarboxylative thioacylation between 45 and threonine derivative 46 furnished thioamide 47 in 71% yield, which was directly converted into thiazoline 49 after treatment with N , N -diethylaminosulfur trifluoride (DAST), followed by reduction with DIBAL-H (Scheme A).…”
mentioning
confidence: 99%
“…14–21 Moreover, recently, aryl thiazole has been used as a potent pan-HDAC inhibitor and peroxisome proliferator-activated receptor δ agonist. 22,23 Subsequently, these aryl thiazole derivatives are more potent against human β3 agonists and have excellent selectivity against another human β receptor. 24 This aryl thiazole framework is a promising chemical tool for selective CYP1B1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%